2018
DOI: 10.1021/acs.molpharmaceut.8b00540
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal Irinotecan Achieves Significant Survival and Tumor Burden Control in a Triple Negative Breast Cancer Model of Spontaneous Metastasis

Abstract: Triple negative breast cancer (TNBC) represents a significant therapeutic challenge due to its highly aggressive nature and lack of effective treatment options. Liposomal irinotecan (nal-IRI, ONIVYDE) was approved in 2015 (by the Food and Drug Administration, European Medicines Agency, and Therapeutic Goods Administration) and is a topoisomerase inhibitor indicated, in combination with fluorouracil and leucovorin, for the treatment of patients with metastatic adenocarcinoma of the pancreas after disease progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Liposomal irinotecan (nal-IRI, ONIVYDE) was approved in 2015 [ 105 ]. Since then, new liposomal irinotecan formulations have been developed and used as second-line treatments of metastatic pancreatic cancer [ 106 , 107 ].…”
Section: New Irinotecan Formulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Liposomal irinotecan (nal-IRI, ONIVYDE) was approved in 2015 [ 105 ]. Since then, new liposomal irinotecan formulations have been developed and used as second-line treatments of metastatic pancreatic cancer [ 106 , 107 ].…”
Section: New Irinotecan Formulationsmentioning
confidence: 99%
“…PEGylated liposomal formulation of irinotecan (MM-398) improved the cytotoxic effects of irinotecan in a mouse model of brain metastasis compared to irinotecan monotherapy [ 111 ]. Liposomal formulations of irinotecan are promising new cytotoxic agents that can be utilized to treat other malignancies such as metastatic breast cancer [ 105 ]. Zhang et al [ 112 ] conjugated irinotecan with a series of fatty acids to increase its lipophilicity and allow particles to self-assemble in an aqueous environment in order to protect estrified irinotecan from bond hydrolysis by carboxylesterases.…”
Section: New Irinotecan Formulationsmentioning
confidence: 99%
“…A similar increased incidence of brain metastasis following chemotherapy was also described in the preclinical setting in long-term surviving animals in a mouse model of melanoma metastatic disease [ 28 ] and following trastuzumab treatment in the LM2-4H2N model [ 19 ]. In a separate study performed by our group, a brain metastatic lesion was indeed observed in the LM2-4 model on day 77 post primary tumor removal (56 days later than the study endpoint for this investigation), after the animal received weekly chemotherapy for 9 weeks [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Topoisomerase-I inhibitors have demonstrated activity in mTNBC, but their use has been limited because of poor intratumor exposure and dose-limiting toxicities. 7,8 Incorporating a topoisomerase-I inhibitor with a targeted delivery method, therefore, presents an opportunity to maximize therapeutic potential. On April 22, 2020, the Food and Drug Administration (FDA) granted accelerated approval for the use of sacituzumab govitecan in mTNBC after granting orphan drug, fast track, and breakthrough therapy designations.…”
Section: Introductionmentioning
confidence: 99%